Metabolomics of Cerebrospinal Fluid in Multiple Sclerosis Compared With Healthy Controls: A Pilot Study - Židó, Michal; Kačer, David; Valeš, Karel; Svobodová, Zuzana; Zimová, Denisa; Štětkárová, Ivana (Frontiers in Neurology, 2022)
Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) leading to loss of myelin and axons. Diagnosis is based on clinical findings, MRI and analysis of cerebrospinal fluid (CSF). CSF is ultra-filtrate of plasma and reflects inflammatory processes in the CNS. The aim of this study was to perform metabolomics analysis of CSF in patients after the first attack of MS and healthy controls and try to find new specific analytes for MS including those potentially predicting disease activity at the onset. Methods: We collected CSF from 19 patients (16 females, aged 19-55 years) after first attack of clinical symptoms who fulfilled revised McDonald criteria of MS and CSF of 19 controls (16 females, aged 19-50 years). Analyses of CSF samples were provided by High Performance Liquid Chromatography system coupled with mass spectrometer with high resolution detector (TripleTOF 5600, AB Sciex, Canada). Results: From approximately 130 selected analytes were identified and verified 30 of them. During the targeted analysis, it was found significant decrease of arginine, histidine, and less significant decrease of level of asparagine, leucine/isoleucine and tryptophan, together with significant increase of palmitic acid in the patient group. Conclusions: We observed significant differences of amino and fatty acids in the CSF of newly diagnosed MS patients in comparison to controls. The most significant changes were observed in levels of arginine, histidine and palmitic acid that may predict inflammatory disease activity. Further studies are necessary to support these finding as potential biomarkers of MS.